2013
DOI: 10.1177/0145482x1310700104
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Perceived Computer Competence and the Employment Outcomes of Transition-aged Youths with Visual Impairments

Abstract: Introduction The study reported here explored the relationship between the self-perceived computer competence and employment outcomes of transition-aged youths with visual impairments. Methods Data on 200 in-school youths and 190 out-of-school youths with a primary disability of visual impairment were retrieved from the database of the first three waves (2001–05) of the National Longitudinal Transition Study–2. The relationship between the youths’ self-perceived computer competence and having paid jobs was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
2
23
1
1
Order By: Relevance
“…In addition, this review identified three new predictors (i.e., psychological empowerment, selfrealization, technology skills) of positive postschool outcomes for youth with disabilities. Our results also found that 11 of the 22 studies focused on one specific disability group, including deaf/blindness (Cmar, 2015); (b) deaf/ hard of hearing (Newman, Marschark, et al, 2016); (c) visual impairments (Connors et al, 2014;Zhou et al, 2013); (d) intellectual disability (Park & Bouck, 2018;Simonsen & Neubert, 2013); (e) specific learning disabilities ; and (f) autism spectrum disorder (Shattuck et al, 2012;Wei et al, 2015Wei et al, , 2016Wei et al, , 2017.…”
Section: Resultssupporting
confidence: 69%
“…In addition, this review identified three new predictors (i.e., psychological empowerment, selfrealization, technology skills) of positive postschool outcomes for youth with disabilities. Our results also found that 11 of the 22 studies focused on one specific disability group, including deaf/blindness (Cmar, 2015); (b) deaf/ hard of hearing (Newman, Marschark, et al, 2016); (c) visual impairments (Connors et al, 2014;Zhou et al, 2013); (d) intellectual disability (Park & Bouck, 2018;Simonsen & Neubert, 2013); (e) specific learning disabilities ; and (f) autism spectrum disorder (Shattuck et al, 2012;Wei et al, 2015Wei et al, , 2016Wei et al, , 2017.…”
Section: Resultssupporting
confidence: 69%
“…A study by Zhou et al (2013) was also using data from NLTS2 Wave 3 (2003)(2004)(2005) and the data was analyzed using the Complex Samples module of SPSS 17.0 to compare between two groups of participants. The results of the study show that for inschool adolescents with vision impairment group, gender variables and the severity of vision loss do not significantly affect employment outcomes.…”
Section: Factors Influencing Outcomes For Transition-agementioning
confidence: 99%
“…A study by Pogrund, Darst, and Boland (2013) found that short-term programs are efficient and more than satisfactory in meeting students' needs associated with the areas of ECC. Other research shows the critical of social skills (Botsford, 2014) and assistive technology (Ferronato & Ukovic, 2014;Zhou, Smith, Parker, & Griffin-Shirley, 2013) in accessing employment for people who are blind and visually impaired. Although lots of studies related to intervention to improve the employability of these students had been established, not one of those studies that directly resulted in employment outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…As in Zhou et al (2013), participants self-reported as being totally blind or having low vision: 17 were blind (10 females and 7 males) and 49 had low vision (24 females and 24 males, 1 did not indicate). Mean age was 31 years (median = 27).…”
Section: Participantsmentioning
confidence: 99%